Aplicación del método flipped classroom como estrategia tecnopedagógica para el aprendizaje de la asignatura de informática dirigida a estudiantes de bachillerato de la Unidad Educativa “María Auxiliadora del cantón Chunchi - José Roberto, Tenezaca Quishpi (2021)
ABSTRACT This research was aimed at analyzing the application of the Flipped Classroom method as a tool to improve the learning of the computer science subject aimed at high school students from the “María Auxiliadora” Educational Unit. Methodologically, the study framed within a mixed approach, since techniques and instruments used for the collection of information, as well as for the analysis of the studied phenomenon, which served as the basis for the construction of the proposal. By design, it was a pre-experimental investigation carried out with a pre and posttest, longitudinal level. By the explanatory type - descriptive; bibliographic, documentary and field. In addition, the inductive - deductive and analytical - synthetic method used. The population made up of 95 high school students, the choice of the sample was non-probabilistic and intentional. The verification of the hypothesis was carried out with a significance level of 0.05 after the t-student statistic calculated, the result was -23.37 obtaining a number less than the critical value of t (one tail) which is 1, 66; for this reason the null hypothesis rejected and the researcher's accepted. It concluded that the implementation of the Flipped Classroom method represents a learning alternative, improving the results from 6.20 to 8.98 points out of ten in their quarterly qualification, achieving in them motivation and interest in the use of the virtual classroom, thus developing the abilities and skills in the subject of computer science. Keywords: Tic, flipped classroom, learning, computing. Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324